THE INFLUENCE OF WORK ETHIC AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE OFFICE OF THE REGIONAL REVENUE AGENCY OF PESAWARAN DISTRICT - Kurniasih, Yuli; Zainudin, Bustami (University of Sang Bumi Ruwa Jurai, 2024)
Employee performance management is an important part of the success of an organization, so to optimize employee performance, organizations must pay attention to work standards and the work environment. Pre-research results show that employees still have not reached their best level. This study aims to determine how work ethic and work environment partially and simultaneously impact employee performance at the Pesawaran Regency Regional Revenue Agency. Quantitative research was used. In this study, there were 61 employees. Observation, documentation, and questionnaires are the data collection methods used. The analysis used is multiple linear regression, in which the t test and f test are used to test the hypothesis. The results showed that tcount = ttable, ttable = tcount, and ttable = ttable. In addition, there is evidence that work ethic and work environment affect overall employee performance, as shown by the Fcount = Ftable value. Work ethic and work environment contribute to employee performance at the Regional Revenue Agency of Pesawaran Regency by 91.9 percent, and other factors not examined in this study affect the rest.